Platelet Rich Plasma's Use on Recovering Achilles Tendon Ruptures of Wistar Strain White Mouse - Seprianto Seprianto; Rizki Rahmadian; Benni Raymond; Tofrizal Tofrizal (Indonesian Journal of Multidisciplinary Science, 2023)
Achilles tendon is the most common site of lower extremity tendon rupture. Current treatment has not been able to restore the biological and mechanical properties of the tendon to pre-injure condition. One of the treatments used to improve Achilles tendon healing is the application of PRP.  The research would like to determine the effect of using Platelet Rich Plasma (PRP) on the recovery of tendon rupture in animals model (wistar strain white rats). This is an experimental study with a post-test only control group design using animals model (white rats). This study was conducted at the INA Lab Laboratory, Padang in November 2022. The samples were divided into two groups, the control group and the treatment group where both of these groups were injured and sutured to the tendons. The control group was not given PRP, while the treatment group was given 0.1 cc of PRP. The PRP used was heterologous from healthy human blood. Observations were made after 1 week both groups were maintained and treated. There were 12 white rats which were divided into the PRP group and the control group. The PRP group had a lower histopathological score (5.83) than the control group (10.50). In this study, there was a significant difference between the recovery of tendon ruptures in animal model (white rats) that were given Human Platelet Rich Plasma (PRP) and experimental animals (rats) that were not given PRP (p value 0.007). PRP improves healing in Achilles tendon rupture.